Comparing the Teaching-Learning Process With and Without the Use of Computerized Technological Resources - Casquel Monti Juliani, Carmen Maria [UNESP]; Corrente, José Eduardo [UNESP]; Dell'Acqua, Magda Cristina Queiroz [UNESP] (Lippincott Williams & Wilkins, 2011)
Computerized technological resources have become essential in education, particularly for teaching topics that require the performance of specific tasks. These resources can effectively help the execution of such tasks and the teaching-learning process itself. After the development of a Web site on the topic of nursing staff scheduling, this study aimed at comparing the development of students involved in the teaching-learning process of the previously mentioned topic, with and without the use of computer technology. Two random groups of undergraduate nursing students from a public university in São Paulo state, Brazil, were organized: a case group (used the Web site) and a control group (did not use the Web site). Data were collected from 2003 to 2005 after approval by the Research Ethics Committee. Results showed no significant difference in motivation or knowledge acquisition. A similar performance for the two groups was also verified. Other aspects observed were difficulty in doing the nursing staff scheduling exercise and the students' acknowledgment of the topic's importance for their training and professional lives; easy access was considered to be a positive aspect for maintaining the Web site.
Keywords: Comparative study; Educational technology; Nursing informatics; Nursing teaching; Teaching-learning process